(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Though initially beneficial, the overuse of translation-based exercises in vocabulary education presents serious problems for language learners. Although translation makes learning new words faster, it frequently removes terminology from its native context and favours passive recognition over active application. Additionally, by reinforcing native language thinking, this dependence hinders intuitive language processing and slows the acquisition of fluency. Moreover, the cultural and pragmatic subtleties that are necessary for successful communication are overlooked in translation. Teachers must use a well-rounded strategy that includes contextual and active learning techniques including output-driven activities, lexical chunking, and immersive tasks in order to solve these problems. These techniques not only help students expand their vocabulary but also provide them the ability to speak smoothly and creatively in everyday contexts.